2018
DOI: 10.3390/w10020154
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Antibiotics on Microbial Community Composition in an Estuary Reservoir during Spring and Summer Seasons

Abstract: Abstract:The increased antibiotic pollutants in aquatic environments pose severe threats on microbial ecology due to their extensive distribution and antibacterial properties. A total of 16 antibiotics including fluoroquinolones (FQs) (ofloxacin (OFX), ciprofloxacin (CFX), norfloxacin (NFX)), Sulfonamides (SAs) (sulfamonomethoxine (SMM), sulfadiazine (SDZ), sulfaquinoxaline (SQX)), Tetracyclines (TCs) (tetracycline (TC), doxycycline (DC)), β-lactams (penicillin G (PEN G), penicillin V (PEN V), cefalexin (LEX))… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…Qingcaosha Reservoir is in the middle of the Yangtze River estuary and adjacent to a small island (31 • 27 N; 121 • 38 E), built in 2009 and operational in 2010 with a depth range from 2.5 m to 13.5 m, a designed hydraulic retention time of 25 days and an approximation area of 66.27 km 2 [28,29]. The reservoir supplies 10 million inhabitants in Shanghai city with 7 million m 3 drinking water per day.…”
Section: Study Area and Samplingmentioning
confidence: 99%
“…Qingcaosha Reservoir is in the middle of the Yangtze River estuary and adjacent to a small island (31 • 27 N; 121 • 38 E), built in 2009 and operational in 2010 with a depth range from 2.5 m to 13.5 m, a designed hydraulic retention time of 25 days and an approximation area of 66.27 km 2 [28,29]. The reservoir supplies 10 million inhabitants in Shanghai city with 7 million m 3 drinking water per day.…”
Section: Study Area and Samplingmentioning
confidence: 99%
“…This special issue comprises of 11 research articles that fall within the scope of AMR. Broadly, topics extend from AMR monitoring and surveillance in environmental resources and effluents from water/wastewater treatment plants [32][33][34][35][36][37][38][39], antimicrobial ecological risk assessments of two river reservoir systems in China that are sources of drinking water supply [40,41], and exploring novel strategies of using engineered antimicrobial peptides (AMP) to target specific bacteria to disrupt biofilms that are major causes of chronic and persistent infections [42].…”
Section: Key Outcomes Of This Special Issuementioning
confidence: 99%
“…However, this may present a greater risk for propagation in the environment through transformation and transduction [44]. In another study by Xu et al [34], the authors studied the relationship of 16 antibiotics with environmental water quality parameters and the impact of antibiotic concentrations on the microbial community structure along Qingcaosha Reservoir, the largest estuary reservoir in China. This reservoir has a similar function to the Yellow River, in that it compensates for drinking water shortages in Shanghai.…”
Section: Amr Monitoring and Surveillancementioning
confidence: 99%
“…In recent years, some studies revealed that the reservoir system could influence the residues and composition of antibiotics exported from the river [27]. Until now, several general studies on antibiotics and ARGs in surface water from the Yangtze estuary were published [20,[28][29][30]. However, information about the spatial and time variation, and a comprehensive understanding about a specific area is still lacking.…”
Section: Introductionmentioning
confidence: 99%